Findings of the First ANZICS Conference on the Role of Intensive Care in Rapid Response Teams. Issue 3 (May 2015) - Jones, D.; Hicks, P.; Currey, J.; Holmes, J.; Fennessy, G. J.; Hillman, K.; Psirides, A.; Rai, S.; Singh, M. Y.; Pilcher, D. V.; Bhonagiri, D.; Hart, G. K.; et al.
Rapid Response Teams (RRTs) are specialised teams introduced into hospitals to improve the outcomes of deteriorating ward patients. Although Rapid Response Systems (RRSs) were developed by the intensive care unit (ICU) community, there is variability in their delivery, and consultant involvement, supervision and leadership appears to be relatively infrequent. In July 2014, the Australian and New Zealand Intensive Care Society (ANZICS) convened the first conference on the role of intensive care medicine in RRTs in Australia and New Zealand. The conference explored RRSs in the broader role of patient safety, resourcing and staffing of RRTs, effect on ICU workload, different RRT models, the outcomes of RRT patients and original research projects in the area of RRSs. Issues around education and training of both ICU registrars and nurses were examined, and the role of team training explored. Measures to assess the effectiveness of the RRS and RRT at the level of health system and hospital, team performance and team effectiveness were discussed, and the need to develop a bi-national ANZICS RRT patient database was presented. Strategies to prevent patient deterioration in the 'pre-RRT' period were discussed, including education of ward nurses and doctors, as well as an overarching governance structure. The role of the ICU in deteriorating ward patients was debated and an integrated model of acute care presented. This article summarises the findings of the conference and presents recommendations on the role of intensive care medicine in RRTs in Australia and New Zealand.